2011
DOI: 10.1093/rheumatology/ker236
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung disease and ANCA-associated vasculitis: a retrospective observational cohort study

Abstract: It is important that physicians are aware of this clinical association and the presence of ILD should be considered in all patients with ANCA-associated vasculitis, especially those with MPO-ANCA. The possibility that patients with ILD may subsequently develop features of systemic vasculitis should also be remembered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
137
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(156 citation statements)
references
References 26 publications
8
137
1
10
Order By: Relevance
“…Although this has been previously reported in the literature (4,5,7,8,(27)(28)(29)(30)(31), we analyzed CT images in sequential hospital-based patients before they received treatment and determined the prevalence of each imaging component of ILD (Table 2). Ground-glass opacity was the most prevalent component, which indicates that a large proportion of MPA patients have an active inflammatory process in the lungs before they receive treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this has been previously reported in the literature (4,5,7,8,(27)(28)(29)(30)(31), we analyzed CT images in sequential hospital-based patients before they received treatment and determined the prevalence of each imaging component of ILD (Table 2). Ground-glass opacity was the most prevalent component, which indicates that a large proportion of MPA patients have an active inflammatory process in the lungs before they receive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse alveolar hemorrhage (DAH) is a well-described pulmonary manifestation of small vessel vasculitis (3,6). However, interstitial lung disease (ILD) was recently recognized as a major pulmonary manifestation in patients with MPA (7,8), although its pathogenesis remains largely unknown. Even more intriguingly, a previous histopathologic analysis showed that a wide variety of extravascular pulmonary injuries, including airway lesions, can be observed in patients with AAVs (9).…”
mentioning
confidence: 99%
“…As expected, the prognosis of PF in overlap syndromes is worse than individual entities (Cambridge et al 1994;Derrett-Smith et al 2013;Szücs et al 2007). Also, ANCA positivity in PF can predispose to development of ANCA associated vasculitis (AAV) (Arulkumaran et al 2011). Here, we present a case of PF with RA, scleroderma sine scleroderma (SSS) and AAV which has never been reported before and has a grave prognosis.…”
Section: Introductionmentioning
confidence: 65%
“…The characteristic lung manifestation of MPA is diffuse alveolar hemorrhage caused by pulmonary capillaritis, which has been reported in 12-55% of patients [1]. Pulmonary fibrosis is a less frequently described pulmonary manifestation and may precede, manifest at time of or follow the diagnosis of MPA [1,4]. However, Tzelepis et al reported recently a relatively high prevalence of pulmonary fibrosis in patients with MPA [5].…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse alveolar hemorrhage caused by pulmonary capillaritis is the most common manifestation of respiratory involvement presenting clinically with dyspnea, hemoptysis, cough, pleuritic chest pain and anemia [2,3]. Pulmonary fibrosis is a rarely reported clinical feature and can be seen months to years prior to, at the time of, or years after the diagnosis of MPA [1,4].…”
Section: Pulmonary Fibrosis Presentingmentioning
confidence: 99%